The Effect of Internet of Things (IoT) Implementation on Customer Satisfaction on the PLN Mobile Application - Afif Syaiful Rachman; Erwin Widodo (Jurnal Impresi Indonesia, 2025)
PT PLN (Persero), as the main electricity provider in Indonesia, faces challenges in improving service quality and customer satisfaction in the digital era. The implementation of the Internet of Things (IoT) through the PLN Mobile application, which offers features such as smart meters and real-time consumption monitoring, represents a service transformation strategy. This research aims to analyze the impact of Internet of Things (IoT) implementation on customer satisfaction within the PLN Mobile application. IoT has transformed the energy sector through technologies such as smart meters and real-time electricity monitoring. These features enable customers to manage their billing, receive energy usage notifications, and report outages more efficiently. A quantitative approach was employed using an online survey targeting PLN Mobile users. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate a positive and significant influence of IoT implementation on customer satisfaction. The path coefficient was 0.809, with a t-statistic of 17.001 and a p-value of 0.000. This suggests that the more effectively IoT-based features are utilized—such as real-time monitoring and energy control—the higher the level of customer satisfaction. The findings offer valuable insights for PLN to enhance its IoT capabilities as a strategy to improve service quality and foster long-term customer loyalty.